STANDARISASI PENILAIAN DI MADRASAH: TINJAUAN FILSAFAT KONSTRUKTIVISTIK - Agus Zaenul Fitri (Fak. Tarbiyah UIN Maliki Malang, 2011)
National Standardization of Education (NSE) aims to ensure the quality of national education in forming intellectual, character and civilization of the nation's dignity. NSE improved in a planning, directing, and sustaining in accordance with the demands of changes in local, national, and global. The standardization of education is also expected to move the stakeholders of education and educational managers to compete in improving student quality as the core of education that deliver them to achieve the standards set. Education creating intellectual abilities without wakened conscience would result in a fragile human soul and the hollow in the face real life challenges. Education is expected to have “soul” that inceases values incluiding Intelligenci Quotient (IQ), Emotional Quotient (EQ) and Spiritual Quotient (SQ).